Advances in natural compound-based nanomedicine and the interaction with gut microbiota in ulcerative colitis therapy - Zhang, Jinlan; Sun, Shuhui; Chen, Huan; Feng, Yifan; Li, Ying; Dong, Zhengqi (Frontiers in Pharmacology, 2023)
Ulcerative colitis (UC) is a chronic inflammatory bowel disorder of the large intestines. Previous studies have indicated that gut microbiota plays an important role in the triggers, development, and treatment response of UC. Natural active molecules and their nanoformulations have a huge potential for treating UC.The nanoparticles can regulate gut microbiota and the metabolites, whereas gut microbiota-mediated effects on nanomedicines can also bring additional therapeutic benefits. Therefore, this review aims to integrate current research on natural active molecules-based nanomedicine for UC therapy and their interaction with the gut microbiota. Here, this discussion focuses on the effects and functions of gut microbiota and metabolites in UC. The use of active molecules and the nanoformulation from natural compounds for UC therapy have been provided. The interactions between gut microbiota and nanomedicines are derived from natural products and elucidate the possible biological mechanisms involved. Finally, the challenges and future directions for enhancing the therapeutic efficacy of nanomedicine in treating UC are proposed.